CTLA-4 Engagement Inhibits Th2 but not Th1 Cell Polarisation - Vanessa Ubaldi; Lucia Gatta; Luigia Pace; Gino Doria; Claudio Pioli (Clinical and Developmental Immunology)
CTLA-4 deficient mice show severe lymphoproliferative disorders with T helper sub-population skewed toward the Th2 phenotype. In the present work, we investigated the role of CTLA-4 in T helper cell subset differentiation. Naïve CD4+ cells were stimulated with anti-CD3 and anti-CD28 mAbs in the presence of either IL-12 or IL-4 to induce polarisation to Th1 or Th2 cells, respectively. Under these two polarising conditions cells express comparable levels of CTLA-4. CTLA-4 was stimulated by plastic-bound mAb. The frequency of IFN-γ- and IL-4-producing cells were estimated by FACS analysis. In parallel cultures, polarised Th1 and Th2 cells were re-stimulated with anti-CD3 and anti-CD28 mAbs for 48 h and their culture supernatants analysed by ELISA. Results show that CTLA-4 engagement during differentiation inhibits polarisation of naïve CD4+ cells to the Th2 but not the Th1 cell subset. At variance, once cells are polarised, CTLA-4 engagement inhibits cytokine production in both effector Th2 and Th1 cells. Altogether these data indicate that CTLA-4 may interfere not only in the signalling involved in acute transcriptional activation of both Th1 and Th2 cells but also in the development of one of the Th cell subsets.